Oncologic outcomes of surgical treatment in supraglottic larynx cancer - Akın, İstemihan and Vuralkan, Erkan and Günsoy, Behçet and Saka, Cem and Akçayöz, Nihat and Şimşek, Gökçe (ENT Updates, 2013)
Objective: To evaluate the oncologic results from our experience in performing laryngectomy for patients with supraglottic laryngeal cancer. Methods: Seventy five consecutive patients who underwent laryngectomy for laryngeal cancer in our department from January 1998 to December 2006 have been reviewed. Seventy two males and 3 females were involved. Their ages ranged from 35 to 70 (average 53.64±8.27) years. Reports of the site and stage of tumor, preoperative or postoperative radiotherapy, complications and the histopathologic examination were reviewed. Results: All tumors were squamous cell carcinoma originating at the supraglottis. Most cancers (73.4%) were classified as stage III/IV. Surgical techniques were including supraglottic partial laryngectomy (n=15, 20%), supracricoid partial laryngectomy (n=3, 4%), total laryngectomy (n=57, 76%). Bilateral (73, 97.3%) and unilateral (2, 2.7%) neck dissections were performed. Fourty patients were treated by radiotherapy after surgery. Regional recurrence occurred in 5 cases. Local recurrence occurred in 2 patients. Median follow-up time was 46.25±23.90 months. The overall survivals were 86.6% for all stages. Conclusion: Stage of tumor and neck should be evaluated carefully before the treatment of laryngeal cancer. Treatment should be specific for patient and ideas of patient must be taken into consideration.